Sanksi Pidana Terhadap Pelaku Tindak Pidana Pemilu di Indonesia - I Gusti Bagus Yoga Sastera; I Made Minggu Widyantara; Luh Putu Suryani (Warmadewa Press, 2020)
In a general election, election crime is bound to occur, in the handling of election criminal acts, it is necessary to have regulations regarding the regulation and sanctions against election criminal offenders to achieve legal certainty regarding the handling of election crimes. The purpose of this research is to find out the regulation of election criminal acts and sanctions against election criminal offenders. The research method used is normative research by examining the sources of law from various aspects and using primary legal sources. The results of the research show that election criminal acts are divided into 2 (two) things, namely violations and crimes, however the law does not clearly regulate the qualifications of violations and crimes, which should be made by law to regulate more clearly so that we can know more about the actions that are involved. how it is said to be violations and what actions are called crimes. Furthermore, regarding sanctions and institutions authorized in handling criminal cases, both violations and crimes in criminal elections, are also listed in Law No.7 of 2017 concerning elections. So that with this research the procedures for qualifying the violation, who feel that their rights are being violated, can report to the right institution to handle the case.